180 A Translational Approach to Uterine Fibroids in Black Women and Latinas. (April 2022) - Orellana, Minerva; Stewart, Elizabeth A.; Balls-Berry, Joyce E.; Enders, Felicity
Abstract : OBJECTIVES/GOALS: Uterine fibroids (UF), non-cancerous myometrial neoplasms, affect 11 million women in the US. In qualitative research, experiences of Black women (BW) and Latinas (HL) with UF are understudied. UF etiology is poorly understood, and most symptoms are focused on decreasing UF symptoms. This study will showcase a translational approach in studying UF. METHODS/STUDY POPULATION: A community-engaged research process will be used throughout the study. We have a partnership with the Fibroid Foundation (FF), a UF advocacy organization. For our first aim, we have held community-engagement (CE) studios to provide insight for best practices in creating and implementing culturally appropriate studies with ethnoracially diverse women regarding topics of UF. Our CE studios set the foundation for the second aim, which will be in-depth interviews assessing the sociocultural impacts among pre-menopausal BW and HL with UF. The women will be recruited through the FFs social media platform. To address lack of treatment options in UF, we will be focusing on JAK 2/3 pathway. We will be performing immunofluorescence on tissue microarrays on over 100 patient samples with extensive clinical and survey data. RESULTS/ANTICIPATED RESULTS: We held two CE studios, one with BW with UF and another with HL without UF. These participants were chosen as patient stakeholders. One theme from the CE studio was that both groups mentioned a cultural impact around menstrual health and UF discussions. The participant stakeholders provided insight to other influences in their journey that will be used to develop the interview guide questions for Aim 2. We expect the individual interviews to show similar experiences as our CE studio experiences. We anticipate more in-depth conversations about the sociocultural and ethnoracial factors impacting UF treatment. For Aim 3, we hypothesize that there will be increased JAK 2/3 expression in UF of patients with higher sympton burden and larger fibroid volume. DISCUSSION/SIGNIFICANCE: Implementing a community-engaged research framework provides a foundation for qualitative and translational gynecologic research in BW and HL. This project will contribute insight to their UF experience. There is a lack of innovative treatments, and we have access to valuable patient tissue and data that can be used for potential molecular targets.